2013
DOI: 10.1167/iovs.13-11597
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Baseline Angle Width and Induced Angle Opening Following Prophylactic Laser Peripheral Iridotomy

Abstract: Our results showed significant opening of the anterior chamber angle width after LPI and demonstrated an inverse association between baseline and LPI-induced opening of the anterior chamber angle width, such that eyes with a more crowded anterior chamber angle undergoing LPI had a greater magnitude of increase in anterior chamber angle width after the procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 38 publications
1
22
3
1
Order By: Relevance
“…See et al [29] found an increase of ACA width but no change of ACD in 17 eyes of 17 patients with suspected primary angle closure, primary angle closure, or primary angle closure glaucoma using AS-OCT. Using the AS-OCT in a group of 84 eyes of 52 angle closure suspects, it could be found that prophylactic LPI causes ACA to increase significantly and that narrower angles at baseline before LPI are associated with a more pronounced increase of ACA than wider angles [30]. Lee et al [31] could show that anterior chamber area and ACA increase after LPI in 32 eyes of 32 primary angle closure suspects but decreases again thereafter so that 18 months after LPI, a group of ACA indices are not statistically different from their pre-LPI values anymore.…”
Section: Discussionmentioning
confidence: 99%
“…See et al [29] found an increase of ACA width but no change of ACD in 17 eyes of 17 patients with suspected primary angle closure, primary angle closure, or primary angle closure glaucoma using AS-OCT. Using the AS-OCT in a group of 84 eyes of 52 angle closure suspects, it could be found that prophylactic LPI causes ACA to increase significantly and that narrower angles at baseline before LPI are associated with a more pronounced increase of ACA than wider angles [30]. Lee et al [31] could show that anterior chamber area and ACA increase after LPI in 32 eyes of 32 primary angle closure suspects but decreases again thereafter so that 18 months after LPI, a group of ACA indices are not statistically different from their pre-LPI values anymore.…”
Section: Discussionmentioning
confidence: 99%
“…This procedure has previously been used in our other studies. 1114 The following parameters were derived from the Zhongshan Angle Assessment Program: trabecular-iris space area at 750 μm from the scleral spur, angle opening distance at 750 μm from the scleral spur, anterior chamber area, anterior chamber volume, anterior chamber width, lens vault, iris thickness measured at 750 μm from the scleral spur, iris area, and pupil diameter.…”
Section: Methodsmentioning
confidence: 99%
“…The above-listed ASOCT parameters were defined previously in our other studies 16 17. AOD500 was defined as the length of the line extending from the anterior iris to the corneal endothelium, perpendicular to the line drawn along the trabecular meshwork at 500 μm anterior to the scleral spur.…”
Section: Methodsmentioning
confidence: 99%